Elaboração de um plano de negócio para uma Microcervejaria - Ribeiro Júnior, Luiz Fernando Turrubia (2018)
In Brazil, beer is a product that has gained space in the market. Even with the crisis there has been an increase in the last 3 years in 91% of registered breweries. In this context, it is proposed the elaboration of a Business Plan for a Microbrewery with the objective of analyzing the economic viability of the enterprise. This analysis involves more detailed information about beer production in Brazil, emphasizing micro breweries and the brewing process, even describing the Business Plan, highlighting the main points to be evaluated, such as microbrewery, analysis marketing plan, operational plan and financial plan. The methodology used to prepare the business plan was adapted from the booklet "How to Elaborate a Business Plan" developed by SEBRAE (2013). The microbrewery studied in this work has the capacity to produce fourteen thousand liters per month divided into four different styles of beers. With the elaboration of the business plan, it is observed that the creation of microbrewery is viable and with a profitability rate of 24.58% and a return on investment still in the first half of the year. It should be noted that complementary actions can be taken along the course of the enterprise, given the volatility of the economy. It is concluded that it is extremely necessary to plan each step of the company in order to avoid the maximum of errors.